Camellia (Camellia oleifera Abel.) seed oil promotes milk fat and protein synthesis‐related gene expression in bovine mammary epithelial cells. Issue 1 (5th December 2019) - Zhong, Wanqi; Shen, Jinglin; Liao, Xiandong; Liu, Xinlu; Zhang, Jing; Zhou, Changhai; Jin, Yongcheng
Abstract: Camellia ( Camellia oleifera Abel.) seed oil is a commonly used edible oil of China. In ancient Chinese literature, it is mentioned to be helpful for postpartum repair and lactation in women. Research on camellia seed oil (CO) as a feed additive for dairy cattle is less. We investigated the effect of CO on the expression of milk fat and protein syntheses‐related genes in differentiated bovine mammary epithelial cells (MAC‐T) using soybean oil (SO) as the control. The results showed that CO increased the expression of genes related to de novo synthesis of fatty acids including sterol regulatory element‐binding protein 1 (SREBP1), acetyl‐CoA carboxylase 1 (ACC), fatty acid synthase (FASN), lipoprotein lipase (LPL), and stearoyl‐CoA desaturase (SCD) ( p  < .05). Among the milk protein genes analyzed, CO increased β‐casein mRNA expression ( p  < .05) and decreased αS1‐casein mRNA expression ( p  < .05) in MAC‐T cells. CO upregulated the pathways related to milk protein synthesis with increased mRNA levels of phosphoinositide 3‐kinase (PI3K), RAC‐alpha serine/threonine‐protein kinase (AKT1), and mammalian target of rapamycin (mTOR) ( p  < .05) in MAC‐T cells. Ribosomal protein S6 kinase beta‐1 (S6K1) gene was upregulated, and eukaryotic initiation factor 4E (eIF4E) gene ( p  < .05) was downregulated with CO treatment. The mRNA expression levels of janus kinase 2 (JAK2), activator of transcription 5‐β (STAT5‐β), and E74‐like factor 5 (ELF5) were elevated in MAC‐T cells treated with CO ( p  < .05). Meanwhile, the protein expression levels of S6K1, STAT5‐β, phosphorylated mTOR (p‐mTOR), p‐S6K1, and p‐STAT5‐β increased in MAC‐T cells treated with CO ( p  < .05). In summary, CO promoted β‐casein synthesis by regulating PI3K‐mTOR‐S6K1 and JAK2‐STAT5 signaling pathways and influenced fatty acid synthesis by regulating SREBP1‐related genes in MAC‐T cells. We need to further confirm the function of CO using in vivo models. Abstract : Camellia ( Camellia oleifera Abel.) seed oil activated genes related to de novo synthesis of fatty acids through SERBP1 signaling pathway and promoted the synthesis of β‐casein through PI3K‐AKT‐mTOR‐S6K1 and JAK2‐STAT5 signaling pathways.